Spider-man: far from home ebook Middle grade novel. - Chhibber, Preeti (Spider-Man: Far from Home., 2019)
Peter Parker's off to Europe with his classmates from school! How does Spider-Man stay one step ahead of the bad guys while on the road, while keeping his identity a secret? You can find that out—and a whole lot more—in this book filled with epic writings from Peter and his best friend Ned. With the help of MJ, Peter and Ned have jotted down all the exciting things they saw while traveling through Europe: favorite foods, photo ops, Spidey-secrets, and more. This ultimate travel journal has it all!